Pemikiran Al-Maqrizi tentang Inflasi dan Relevansinya terhadap Fenomena Kenaikan Harga Pangan di Indonesia - Emil Saeful Milah; Sany Nur Ihsan; Lina Marlina; Ana Fauziya Diyana; Muhamad Irfan Fadilah (Economie: Jurnal Ilmu Ekonomi, 2026)
Inflation is an economic phenomenon characterized by a general increase in the prices of goods and services over a certain period, which can affect economic stability and public welfare. In Indonesia, food price increases often become a major contributor to inflation because they are closely related to the basic needs of society. This study aims to examine Al-Maqrizi’s thoughts on inflation and analyze their relevance to the phenomenon of rising food prices in Indonesia. This research uses a descriptive qualitative approach with a library research method by reviewing various sources such as books, scientific journals, and academic articles related to the concept of inflation in Islamic economics. The results show that Al-Maqrizi classified inflation into two types: natural inflation, which is caused by natural factors such as disasters and crop failures, and human error inflation, which arises from human actions such as corruption, inappropriate economic policies, hoarding practices, and poor governance. The phenomenon of rising food prices in Indonesia indicates that these two factors remain relevant in explaining current inflation dynamics. Therefore, controlling food inflation requires not only economic policies focused on production but also improvements in distribution systems, market supervision, and the implementation of justice principles in economic activities.